FENOMENA POLA KOMUNIKASI DAN GAYA HIDUP TRANSGENDER DI PEKANBARU (PENDEKATAN KONSTRUKSI REALITAS SOSIAL : PEMIKIRAN PETER L. BERGER TENTANG KENYATAAN SOSIAL) - Sartika; Hari Jummaulana; Ermairel Salim; Sri Wahyuni; Milla Mantia Suci (JURNAL SOSIO-KOMUNIKA, 2023)
This study aims to find out the phenomena in transgender life both in communication and social life. The application of supporting theory in this problem is by discussing communication patterns within the family (internal) scope and Peter L.Berger's approach of thinking which discusses the social reality of a transgender person. This research method uses a qualitative phenomenological approach, data collection techniques using free interviews addressed to informants based on criteria according to the researcher's assessment. The results of this study are the existence of communication patterns within the family as one of the factors in assessing one's identity towards the environment. As well as to explore this problem, a real-life thinking approach is needed, namely Peter L. Berger's approach in which in examining a person's life it is seen from several supporting factors, so that transgender people can describe the reality of their life based on these factors.